Locally Relevant High‐Resolution Hydrodynamic Modeling of River Floods at the Regional Scale - Buttinger‐Kreuzhuber, Andreas; Waser, Jürgen; Cornel, Daniel; Horváth, Zsolt; Konev, Artem; Wimmer, Michael H.; Komma, Jürgen; Blöschl, Günter (Water resources research, 2022)
This paper deals with the simulation of inundated areas for a region of 84,000 km2 from estimated flood discharges at a resolution of 2 m. We develop a modeling framework that enables efficient parallel processing of the project region by splitting it into simulation tiles. For each simulation tile, the framework automatically calculates all input data and boundary conditions required for the hydraulic simulation on‐the‐fly. A novel method is proposed that ensures regionally consistent flood peak probabilities. Instead of simulating individual events, the framework simulates effective hydrographs consistent with the flood quantiles by adjusting streamflow at river nodes. The model accounts for local effects from buildings, culverts, levees, and retention basins. The two‐dimensional full shallow water equations are solved by a second‐order accurate scheme for all river reaches in Austria with catchment sizes over 10 km2, totaling 33,380 km. Using graphics processing units (GPUs), a single NVIDIA Titan RTX simulates a period of 3 days for a tile with 50 million wet cells in less than 3 days. We find good agreement between simulated and measured stage–discharge relationships at gauges. The simulated flood hazard maps also compare well with local high‐quality flood maps, achieving critical success index scores of 0.6–0.79. Key Points Second‐order accurate scheme discretizing the full shallow water equations at a resolution of 2 m for a stream network of 33,880 km length Streamflow adjustment for regionally consistent flood peak probabilities and automatic estimation of boundary conditions for arbitrary domain tiling Model accuracy comparable to local models (critical success index scores of 0.6–0.79)